Investigation of the effects of the social power and social distance on the realization of apology between Jordanian and English cultures - Al-Khaza'leh, Bilal Ayed; Zainal Ariff, Tun Nur Afizah (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
The current study investigated the influence of context-external variables; social power (High, Equal and Low) and social distance (Familiar and Unfamiliar) on the perception of Jordanian and English speech act of apology. Discourse Completion Test (DCT) and Scaled Response Questionnaire (SRQ) were used to elicit data from three groups: 40 Jordanian L2 speakers in Malaysia, 40 Jordanian non-English speakers in Malaysia and 40 English native speakers from British Council in Jordan. The three groups of respondents were asked to assess four context-internal variables i.e. the severity of the offence, the possibility of the offender apology, the difficulty of the apology by the offender and the likelihood of apology acceptance by the offended party. Results of the study were accomplished using one way ANOVA and Tukey HSD post hoc statistical tests. The findings revealed that Jordanians have high sensitivity toward hierarchical power and social distance more than English native speakers. Moreover, results revealed that there are negative sociopragmatic transfers from L1 to L2 by JL2Ss based on their four-context internal variables perception. Findings could be used to increase the cultural awareness toward some similarities and differences between both cultures